Role of The Youth Counseling Information Center (PIK-R) in Efforts to Improve Teenager's Attitudes in The Prevention of Early Marriage - Levi Tina Sari; Ika Agustina; Wardah Audina (STIKes Patria Husada Blitar, 2023)
Early marriage among young women will cause reproductive health problems, namely unpreparedness of the reproductive organs, unwanted pregnancies, unsafe abortion practices, and even young women who have narrow hips, which will hinder the birthing process and can even cause the death of the mother and child. To prevent early marriage, PIK-R is needed. The education provided in PIK-R is about the 8 functions of the family, the KRR Triad (Adolescent Reproductive Health), education on Marriage Age Maturation (PUP) and Delaying First Children (PAP), as well as providing an understanding of the role of teenagers in social life. This research used a Pre-Experimental research design with a one group pre-post test approach. The total population is 33 children. The sample in this study was 30 respondents used the Slovin formula. Result was increase in the mean between before and after of 1.5 points, meaning there was a tendency for good attitudes after treatment, method of providing education using FGD. It is known that the 2-tailed significant value is 0.0001 < α 0.05, so there is a difference between before and after treatment. The FGD method applied by PIK-R cadres can be an efficient health education approach for teenagers to prevent increasing cases of early marriage. Discussions among teenagers and by teenagers are more open and will produce active communication among teenagers.